2014
DOI: 10.1111/bjh.12749
|View full text |Cite
|
Sign up to set email alerts
|

Clinical value of pre‐transplant minimal residual disease in childhood lymphoblastic leukaemia: the results of the French minimal residual disease‐guided protocol

Abstract: SummaryMinimal residual disease (MRD) is a major predictive factor of the cure rate of acute lymphoblastic leukaemia (ALL). Haematopoietic cell transplantation is a treatment option for patients at high risk of relapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
27
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 50 publications
5
27
0
Order By: Relevance
“…This confirms the major role of antithymocyte globulin as part of GvHD prophylaxis in patients transplanted from unrelated donors. 11 We also report a low rate of TRM compared with other series where average TRM reaches 20-25%, 25,29,30,34 even though a large variability (7-45%) is possible. 27,35,38,39 Our results suggest that close monitoring of CsA therapy may permit a substantial reduction of GvHD-related mortality.…”
Section: Discussionsupporting
confidence: 49%
See 4 more Smart Citations
“…This confirms the major role of antithymocyte globulin as part of GvHD prophylaxis in patients transplanted from unrelated donors. 11 We also report a low rate of TRM compared with other series where average TRM reaches 20-25%, 25,29,30,34 even though a large variability (7-45%) is possible. 27,35,38,39 Our results suggest that close monitoring of CsA therapy may permit a substantial reduction of GvHD-related mortality.…”
Section: Discussionsupporting
confidence: 49%
“…Second, as this study is monocentric, patients in this study did not receive various combinations of immunosuppressive agents as usually reported. 25,28,30,35,54 MRD before HSCT had no prognostic value in our cohort. The DFS of patients with negative or positive MRD before HSCT was similar.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations